Analisis Usaha Agroindustri Penggilingan Padi Kecil Di Kabupaten Sragen - Ahmad Gilang Saputro; Suprapti Supardi; Susi Wuri Ani (Universitas Sebelas Maret, 2018)
Rice Milling Agroindustry was a business engaged in time after rice harvest that would process dry milled rice (GKG) into rice. This study aims to obtained cost, income, income and break even point (BEP) in unit (Kg) and price (Rp) of small agroindustry rice mill in Sragen regency. The basic method of research used analytical descriptive method with survey technique. Determination of location of sample sub- district was done by purposive, that was Kedawung, Masaran and Tanon Subdistrict. Respondents were taken with purposive sampling of 30 people. The types and sources of data used from the primary and secondary data. Technical data was done by interview, observation and documentation. The results showed the average amount of operating revenues of IDR 3,440,880,724/year and IDR 478,41,.307/year. The fficiency of the business were 1.16 and can be said to be efficient because the R/C ratio was more than one. Break even point (BEP) of Small rice milling agroindustry business on the basis of price (IDR) has their breakeven business position broken down by the main output of brown rice from IDR 508,027,645, white rice IDR 30,825,245, gloss rice at IDR 181,746,850. BEP on the basis of unit with main product of white rice was equal to66,610 Kg, 36,588 kg of gloss of rice, brown rice of 109.963 Kg.